An Internet of Things (IoT) Application for Standard Clinical ECGâ€™s Monitoring in Real Time Application - Hadiyoso, Sugondo; Rizal, Achmad; Alfaruq, Akhmad (International Journal of Engineering and Technology, 2019)
Real-time monitoring application of vital body signals gets particular attention in medical research, no exception to the use of IOT applications. The focus of this paper is the acquisition of 12 lead ECG signals from the patient's body and then sending data to the cloud and widely accessible through the Internet instantly. In the measurements process, the device at the patient's side is connected to the receiver application through the Internet by accessing the web server address. At that moment, the data ECG signal is sent to be displayed on the application side. Graph of ECG signals appears on web pages live and continue until the end of the measurement. Medical record system is also applied to this system. By monitoring the ECG signal from the ECG standard instruments can help diagnose heart health in detail. Medical experts can determine the heart conditions and can provide treatment as soon as possible.Â Â